Proceedings of the 3d International ICST Conference on Pervasive Computing Technologies for Healthcare 2009
DOI: 10.4108/icst.pervasivehealth2009.6033
|View full text |Cite
|
Sign up to set email alerts
|

Wearable sensors for pervasive healthcare management

Abstract: We show that it is possible to identify individual personality traits and measure group performance in a Postanesthesia Care Unit (PACU) using wearable sensors. We instrumented a group of 67 nurses working in the PACU of a Boston area hospital with sociometric badges capable of measuring physical activity, speech activity, face-to-face interaction, and physical proximity. Using the data collected with these sensors we were able to estimate the daily average length of stay (LOS) and number of delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 11 publications
2
48
0
Order By: Relevance
“…According to [46], Conscientiousness negatively correlates with closeness, betweenness and degree centrality; Extraversion and Neuroticism (the latter in a less evident manner) positively correlate with degree, closeness, betweenness and eigenvector centrality. Olguin et al [36] obtained evidence for the negative correlation of Conscientiousness and betweenness centrality. In a more recent study conducted by Gloor et al [17], the authors found significant positive correlations between Openness and Agreeableness and degree and betweenness centrality.…”
Section: Centrality Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [46], Conscientiousness negatively correlates with closeness, betweenness and degree centrality; Extraversion and Neuroticism (the latter in a less evident manner) positively correlate with degree, closeness, betweenness and eigenvector centrality. Olguin et al [36] obtained evidence for the negative correlation of Conscientiousness and betweenness centrality. In a more recent study conducted by Gloor et al [17], the authors found significant positive correlations between Openness and Agreeableness and degree and betweenness centrality.…”
Section: Centrality Measuresmentioning
confidence: 99%
“…Recently, however, researchers in social and ubiquitous computing have started exploring the wealth of behavioral data made available by smartphones, wearable sensors (e.g., sociometric badges [36]), Facebook [39] and Twitter [18,38]. Exploiting sociometric badges, Olguin et al [36] found that Extraversion and Neuroticism were positively correlated with degree, closeness, betweenness, and eigenvector centrality measures. Moreover, they found a negative correlation between Conscientiousness and betweenness centrality.…”
Section: Previous Work In Social and Ubiquitous Computingmentioning
confidence: 99%
“…These studies use the abundance of personal data from different domains such as short essays, blog posts [21], social media profiles [18], surveillance with wearable sensors [22,23], computer game behavior [24] and videos containing interaction between people [10,17,20].…”
Section: Prediction Of Personality Traitsmentioning
confidence: 99%
“…The sociometric badge collects communication patterns of individuals by monitoring physical proximity, physical activity levels, and conversational times to quantify social interactions, group behavior, and organizational dynamics. It has also been used in the context of personal healthcare management [13]. The personal digital assistants designed by Wyatt et al [21], contain 8 different sensors to capture human conversations over time.…”
Section: Related Workmentioning
confidence: 99%